CHEMICAL COMPOSITION OF THE UROLOGY COLLECTION - Farmanova, Nodira Takhirovna; Pulatova, Lola Tairkhanovna; Mambetova, Dildor Irgashevna; Nurullaev, Arzikul Dzhurakulovich; Khudoykulova, Dlafruz Kabiljanovna (Химия растительного сырья, 2021)
In order to identify the main biologically active complex, there were carried out a chemical analysis of the urological collection. As a result of the study, there were established the presence of water-soluble polysaccharides in the urological collection 3.2±0.3%, amino acids – 406.3±0.01 nmol, ascorbic acid 45.0±0.5 mg%, carotenoids 0.50±0.04 mg%, organic acids 1.87±0.2%, essential oil – 0.79±0.1%, flavonoids – 0.43±0.04%, coumarins – 0.18±0.2%, phenolcarboxylic acids – 0.41±0.2%, tannins – 5.3±0.4%, saponins (glycyrrhizic acid) – 1.15±0.2%, as well as macro- and micronutrients – 19596.65±0.002 mg/kg. The elemental composition of the collection is represented by 17 vital elements (K, Ca, Mg, Na, P are the dominant components). During studies have also shown the presence of 14 amino acids, 7 of which are essential (44.6% of the total amino acids). It can be clearly stated that the indicator components of the collection are polyphenolic compounds (flavonoids, tannins, etc.) and saponins (glycyrrhizic acid) predominantly passing into aqueous extracts (the proposed dosage form) of the collection, the complex of which determines the specific activity of the studied urological collection. The obtained data were used to develop the authenticity and criteria of the quality of the studied collection.